The Results of Uterine Prolapse Surgery in Elderly Woman with Partial Colpocleisis Procedure and Anterior Posterior Vaginal Repair - อธิรัตน์ปัญญา นพดล (Journal of Preventive Medicine Association of Thailand, 2019)
This prospective study aims to show the results of uterine prolapse surgery with partial colpocleisis procedure and anterior posterior repair in elderly women from Khaoyoi and Banlart hospital Petchaburi Province during August 2008 and August 2015. The objective of this study was to show the underwent prolapse repair, the duration of operation times, the complication of intraoperation, post operation and the results for correcting uterine prolapse. There were 25 patients whose the age of 70 and over. The average age was 74.6 years (SD = 13.42). The average operation time was 56.8 minutes (SD = 43.5). There were 24 (96%) successful cases in this study. There were 2 cases with intraoperative complications from mild hypoglycemia. There was 1 case recurrence of uterine prolapse and was successfully treated with complete colpocleisis operation. The results from this preliminary study showed that partial colpocleisis procedure and anterior posterior repair offers significant advantages in elderly patients in whom conservative management is not feasible.